2012
DOI: 10.1007/s10120-011-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase-II trial comparing sequential and concurrent paclitaxel with oral or parenteral fluorinated pyrimidines for advanced or metastatic gastric cancer

Abstract: Background The purpose of this study was twofold: (1) to compare S-1 with infusional 5-fluorouracil (FU) to determine which would be a better partner of paclitaxel (PTX), and (2) to compare a concurrent strategy with a sequential one, the latter strategy being the one that is widely used in Japanese general practice. Methods The 161 eligible patients were randomized into four arms to receive the following regimens: A (sequential), intravenous 5-FU at 800 mg/m 2 for 5 days every 4 weeks followed by weekly PTX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Recently, the feasibility of SC was tested in an adjuvant setting to see whether this combination regimen is suitable for a test arm of a future Phase III trial which revealed that SC was not tolerable when it was started just after surgery, but was feasible and safe when provided preoperatively [53][57]. Paclitaxel is another key drug used for metastatic disease and has been tested in an adjuvant setting in a phase III trial [58], [59]. Moreover, paclitaxel plus DDP (PC) demonstrated a high response rate and feasibility for metastatic disease [58].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the feasibility of SC was tested in an adjuvant setting to see whether this combination regimen is suitable for a test arm of a future Phase III trial which revealed that SC was not tolerable when it was started just after surgery, but was feasible and safe when provided preoperatively [53][57]. Paclitaxel is another key drug used for metastatic disease and has been tested in an adjuvant setting in a phase III trial [58], [59]. Moreover, paclitaxel plus DDP (PC) demonstrated a high response rate and feasibility for metastatic disease [58].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared S-1 alone with 5-FU alone (S-1 vs 5-FU), [14,17] 3 compared S-1 plus cisplatin with 5-FU plus cisplatin (SP vs FP), [13,15,16] and 2 compared S-1 plus paclitaxel with 5-FU plus paclitaxel (SPtx vs FPtx). [11,12] Regimens were similar with respect to doses and schedules in every trial. There were no significant differences in the baselines between S-1-containing and 5-FU-containing groups in these studies as reported.…”
Section: Resultsmentioning
confidence: 92%
“…[17] The main characteristics of the included trials were shown in Table 1. Six studies were performed in East Asia (3 in Japan [12,14,17] and 3 in China [11,15,16] ), and the remaining study was a non-Asian global phase III trial performed in 24 countries. [13] All studies were multicenter in nature, involving 8 to 146 centers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations